Building community? The characteristics of America's most civic cities1. Issue 1 (28th April 2015) - Engbers, Trent A.
Abstract : A tremendous amount is known about individual civic and political participation. Those who participate are more educated, more affluent and easier to mobilize. Yet, the social value of participation lies not in its individual impact but in democratically meaningful units such as local governments. Little is known about why some communities display vibrant patterns of participation while others are characterized by disengagement. This paper furthers this understanding by examining what corporate, political and nonprofit leaders in 10 America's cities see as fostering their civic life. This study finds that institutional factors unite those cities with the highest levels of participation. These include a strong corporate presence, mechanisms for mobilization, a strong community identity, public spaces, good government and investment in youth. This serves as a basis for fostering pro‐civic policies. This is a practitioner‐oriented paper that while grounded in research is designed to foster policy solutions rather than prove casual mechanisms. Copyright © 2015 John Wiley & Sons, Ltd.